Retrocardiac Opacities Detected on Chest Radiographs and their Imaging Workup: A Pictorial Review - Saikumar, Divya; Ramachandran, K.; Zunimol, P.K.M. (Indographics, 2023)
The retrocardiac space is a tricky area in the chest radiograph, where abnormal densities are frequently missed out. Lesions in this area produce late pressure symptoms compared with those in the upper mediastinum. Early detection and proper evaluation of retrocardiac opacities can help the radiologist to establish the diagnosis before clinical signs and symptoms become apparent. We present a case series of 10 patients with incidentally detected retrocardiac opacities in the frontal chest radiograph, which were further evaluated with other imaging modalities such as lateral chest radiograph, computed tomography (CT) or magnetic resonance imaging (MRI) to establish the diagnosis. The final diagnosis included congenital conditions like esophageal duplication cyst and bronchogenic cyst; inflammatory conditions like spondylodiscitis, lung abscess, and lobar pneumonia; vascular conditions like aortic aneurysm; diaphragmatic pathologies like hiatus hernia; and rare tumors like cardiac papillary fibroelastoma, pulmonary neuroendocrine tumor, and ganglioneuroma. Cardinal signs that aid in the diagnosis of retrocardiac opacities are also discussed.
Keywords: retrocardiac opacities; retrocardiac space; chest radiograph; retrocardiac sail sign; cardiac shadow